2019
DOI: 10.18196/jai.2003128
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing, Organizational Culture, Intellectual Capital, and Organizational Performance

Abstract: This study aims to examine the influence of knowledge sharing and organizational culture toward organizational performance with intellectual capital as an intervening variable. The questionnaire was sent to 71 general managers of manufacturing companies, and 60 questionnaires were returned. The data of this research were analyzed using structural equation modelling (SEM) method, with Partial Least Square (PLS) approach. The results of this study indicated that knowledge sharing had a significant positive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…Tobin Q yang digunakan pada penelitian ini dihitung dengan rasio Q yang telah di modifikasi oleh Lee et al (2019). (Irawan et al, 2019).…”
Section: Nilai Perusahaanunclassified
“…Tobin Q yang digunakan pada penelitian ini dihitung dengan rasio Q yang telah di modifikasi oleh Lee et al (2019). (Irawan et al, 2019).…”
Section: Nilai Perusahaanunclassified
“…Studies by Migdadi, Zaid, Zaidbauedujo, Yousif, and Al-hyari (2017); Balasubramanian, Al-Ahbabi, and Sreejith (2019) and Tarhini et al (2017) showed the effect of knowledge management on the performance of organizations in the Thai food industry. The study by Irawan, Bastian, and Hanifah (2019) mentioned that knowledge management, specifically knowledge distribution, had a positive influence on performance. Wendra and Alhadar (2020) discovered that knowledge management directly affects innovational performance.…”
Section: Discussionmentioning
confidence: 99%
“…Many organisations have realised the importance of securing intangible assets in a knowledge-based economy instead of tangible assets to improve organisational performance. Intangible assets are non-physical assets owned by the organisation for producing goods or delivering services, administrative purposes, and future investment (Irawan et al, 2019). Intangible assets also refer to the firm's intellectual capital (IC), including the employees' knowledge, capabilities and experience, technology, and the ability to create innovation (Chen, 2007;Huang & Kung, 2011).…”
Section: Top Of Formmentioning
confidence: 99%